Atypical haemolytic-uraemic syndrome caused by factor H mutation: case report and new management strategies in children - Araújo, L. (2012)
Atypical haemolytic uraemic syndrome is causedby alternative complement pathway dysregulation. It has recently been recognised that most cases are due to genetic factors and a growing list of mutations has been described. Atypical haemolytic uraemic syndrome is associated with a dismal prognosis, a relapsing course, high acute mortality and frequent progression to end-stage renal disease. We describe a five-year-old boy admitted with a first recurrence of atypical haemolytic uraemic syndrome. The primary onset of the disease was at 15 months of age, following which there was complete recovery of haematological and renal parameters. His family history was significant in that his mother had died at the age of only 23 years of a stroke with associated thrombotic microangiopathy, suggesting a familial form of the disease. Sequencing of the gene encoding complement factor H revealed a heterozygous SCR20 mutation (3644G>T, Arg1215Leu), confirming the diagnosis. The patient was successfully treated with fresh frozen plasma infusions that induced disease remission. We also review currently evolving concepts about atypical haemolytic uraemic syndrome caused by factor H mutation, its diagnosis, the role of genetic testing and management strategies in children.